Dispute Settlement in the World Trade Organization : Practice and Procedure - Palmeter, David; Mavroidis, Petros C. (Cambridge : Cambridge University Press, 2004)
Any experienced lawyer knows that cases are most often won or lost on procedural grounds; yet procedural issues are often considered too technical for proper treatment in legal literature. In this extensively revised 2004 edition of Palmeter and Mavroidis' authoritative book on WTO dispute settlement, the authors discuss all WTO dispute settlement provisions and their interpretation in WTO jurisprudence. All the decisions of panels and the Appellate Body are discussed, from the inception of the WTO in 1995 until the end of May 2003. Although the book contains considerable technical expertise, it is at the same time written for accessibility to a wide readership. This volume - an essential tool for practitioners, diplomats and government lawyers - is a comprehensive study of compulsory third party adjudication in international law.
Title from publisher's bibliographic system (viewed on 02 May 2017).
Keywords: World Trade Organization; Arbitration and award, International; Arbitration agreements, Commercial; Foreign trade regulation